Analysis, Properties, and Applications of Insect-Derived Chitosan: A Sustainable Path to Functional Polysaccharide Materials - Hanna L. Schäfer; Lars Gandras; Laura Schneider; Marco Witthohn; Kerstin Troidl; Kai Muffler; Clemens K. Weiss (Gels)
Chitin and its deacetylated derivative, chitosan, are biopolymers of significant interest due to their biocompatibility, biodegradability, and wide-ranging applications in biomedical, environmental, and industrial fields. The exploitation of crustaceans as the traditional source of chitosan raises concerns about overfishing and ecological sustainability. Modern insect farming, in contrast, offers advantages such as a circular insect-based economy leading to a reduced carbon footprint. This review explores the potential of insect-derived chitosan as an alternative, emphasizing its environmental benefits during production, functional properties, and potential applications. Several aspects of key analytical techniques for chitin and chitosan characterization, including photometric, chromatographic, and spectroscopic methods, are also discussed. The review underscores the versatility of insect-derived chitosan in biomedical applications, including wound healing and drug delivery, as well as its potential in agriculture, packaging, and wastewater treatment.